The Religious Pluralism and the Claims of Metaphysical Truth: An analysis in the light of Sri Ramakrishna's Thoughts - Shubhrajyoti Visvabharati (Tattva Journal of Philosophy, 2023)
The genesis of all religious conflicts lies at the level of Metaphysical claims. Though attempts have been made to reconcile the differences, most of these endeavours have followed the Hermeneutics of Western tradition. The paper attempts to develop a paradigm of looking at different claims in the light of a cross-cultural Hermeneutics. It works with the hypothesis that if philosophical conflicts within a school can be resolved by a proper interpretation, the same principle could be applied to resolve all inter-religious conflicts. For that purpose, it analyzes the thoughts of Sri Ramakrishna in the light of the Upaniṣads and attempts to resolve the conflicts within Vedānta; as a model. It claims that even without resorting to so called reconcilliation, religious conflicts could be resolved if one can realize that all the theories, at par, are representation of the same Truth. It further challenges undue realiance on the Western model of Logic and argues that Sri Ramakrishna’s discourse on the Ultimate Reality opens up the possibility of such an understanding. In lieu of creating intellectual models to create harmony, the ability to transcend intellectual meaning perhaps would be a better way to preserve Religious Pluralism.